The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21608/ejchem.2021.101614.4727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano, bio, chemical fertilization and leaves extract of moringa plant on flowering and chemical constituents of gladiolus plant

Abstract: Pot experiments were carried out during two successive seasons of 2018/2019 and 2019/2020 at the experimental farm of Horticulture Research Institute, Agricultural Research Center, Giza, Egypt to study the effect of different types of fertilizers, traditional NPK (t-NPK) at 2.0 g/pot, nano NPK (n-NPK) at 0.5 and 1.0 g/l, active dry yeast extract (ADYE) at 5.0 and 10.0 g/l, moringa leaves extract (MLE) at 5.0 and 10.0%, and some combinations (ADYE at 5.0 g/l + MLE at 5.0%, MLE at 10% + n-NPK at 1.0 g/l and ADYE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
3
1
0
Order By: Relevance
“…al., (2008) who reported that number of flowers was in consistence with leaves number under P treatments. The outcomes were also in compatible with Sarhan et. al.…”
Section: Results and Discussion 1-vegetative Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…al., (2008) who reported that number of flowers was in consistence with leaves number under P treatments. The outcomes were also in compatible with Sarhan et. al.…”
Section: Results and Discussion 1-vegetative Parameterssupporting
confidence: 89%
“…Each of nano-NPK treatment (0.5 ,1 g L -1 ) was superior over treatments of traditional NPK and control in chlorophyll a, b, and carotenoids, and carbohydrates. The same nano treatment also recorded the higher percentages of N%, P%, K% compared to basic treatment or control (Sarhan et. al., 2022).…”
Section: Introductionmentioning
confidence: 86%
“…It is noticed from the former studies that there are some plants gave similar results to obtained in this study when treated with yeast extract such as Vicia faba plant (Mady, 2009), Citrus aurantifolia (Mustafa et al, 2019), potato (Manea et al, 2019), Ocimum basilicum (Mohamed et al, 2022), Gladiolus grandiflorus (Sarhan et al, 2022). The improvement effect of the foliar application of yeast extract may be attributed to its bioregulator role in plants, affecting the balance of photosynthesis and photorespiration (Olaiya, 2010) and delaying the leaf senescence by reducing the degradation of chlorophyll, improving protein and RNA synthesis (Youssef et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…The effect of yeast extract was reported also by Parađiković et al (2019) on some horticultural plant species. In this aspect, many studies showed that the enhancement effect of algae extract on macronutrient elements content (Tarraf et al, 2015), total sugars content (Hamouda et al, 2022).The similar results for the effect of yeast extract on macronutrient elements were obtained by many authors on (Mady, 2009;Mustafa et al, 2019;Manea et al, 2019;Sarhan et al, 2022 andYoussef et al, 2022).…”
Section: Discussionsupporting
confidence: 55%